2015
DOI: 10.1016/j.jaci.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase inhibition blocks asthma in mice and modulates human endothelial and CD4+ T-cell function without causing severe combined immunodeficiency

Abstract: Background We reported that DNA-PK is critical for the expression of NF-κB-dependent genes in TNF-α-treated glioblastoma cells, suggesting an involvement in inflammatory diseases. Objective To investigate the role of DNA-PK in asthma. Methods Cell culture and ovalbumin or house dust mite (HDM)-based murine asthma models were used in this study. Results DNA-PK was essential for monocyte adhesion to TNF-α–treated-endothelial cells. Administration of the DNA-PK inhibitor, NU7441, reduced airway eosinophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 21 publications
7
63
1
Order By: Relevance
“…Although measuring lung resistance is considered a more reliable way of evaluating the lung function, Penh has been shown to correlate well with invasive measures of AHR . Moreover, our studies consistently showed an increased AHR in allergen‐exposed C57BL6 mice compared to control mice . In line with these reports, AHR to methacholine was significantly increased in OVA‐sensitized and challenged mice versus controls, while etomoxir‐treated mice had a significant reduction in AHR (Figure B).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Although measuring lung resistance is considered a more reliable way of evaluating the lung function, Penh has been shown to correlate well with invasive measures of AHR . Moreover, our studies consistently showed an increased AHR in allergen‐exposed C57BL6 mice compared to control mice . In line with these reports, AHR to methacholine was significantly increased in OVA‐sensitized and challenged mice versus controls, while etomoxir‐treated mice had a significant reduction in AHR (Figure B).…”
Section: Resultssupporting
confidence: 88%
“…For the OVA‐induced asthma model, mice were sensitized by intraperitoneal injection of 50 μg grade V chicken OVA (Sigma‐Aldrich) mixed with 2 mg aluminium hydroxide in saline once a week for 2 weeks. After two weeks, mice were challenged with aerosolized 3% OVA for 30 minutes . Mice were left untreated or treated with intraperitoneal injection of the CPT1 inhibitor etomoxir (Sigma‐Aldrich, St. Louis, MO) or the HADHA inhibitor ranolazine (Sigma‐Aldrich) at 50 mg/kg (both diluted in saline) 30 minutes after challenge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…injection twice, once a week as previously described [16, 17]. Mice were then challenged with aerosolized 3% OVA for 30 min once for the acute model or 3 times per week for 4 weeks for the chronic model.…”
Section: Methodsmentioning
confidence: 99%